STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA SYEKH KATIK SANGKO DI KELURAHAN PASIR KECAMATAN PARIAMAN TENGAH KOTA PARIAMAN - Silvia, Dina; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2019)
This research aimed to (a) describe the structure of folklore legend of Syekh Katik Sangko in Pasir Subdistrict, central Pariaman District, Pariaman City. (b) describe the social function of folklore legend of Sheikh Katik Sangko in Pasir Village, Central Pariaman District, Pariaman City. The type of this research is qualitative research with descriptive methods. The data analysis technique was carried out through four steps. The first step was to carried out data inventory. The second was the data classification or analysis phase. The third step was a discussion and conclusion of the results of classification or data analysis. The last was reporting the research as thesis. The results of this study were found that in the folklore legend of Syekh Katik Sangko in Pasir Subdistrict, central Pariaman District, Pariaman City has 10 figures. The theme in this story is the spreading of Islam in Pariaman. Social functions found are means of education, inheritance and identity.Â Keywords: structure, social function, folklore